2015
DOI: 10.5897/ajfs2015.1373
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus and other Staphylococcus species in milk and milk products from Tigray region, Northern Ethiopia

Abstract: Staphylococcus aureus is an important pathogen that can cause Staphylococcal Food Poisoning (SFP).Milk and dairy products are frequently contaminated by this bacterium. In this study, 310 samples (168 bovine raw milk and 142 dairy products) were collected in the Tigray region of Northern Ethiopia, with the objective of detection and enumeration of S. aureus and other Staphylococcus species. Baird-Parker agar for isolation and 16S rRNA gene sequencing for species identification were employed. S. aureus was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
11
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 32 publications
7
11
3
Order By: Relevance
“…In line with this finding, the overall mean count of 4.35±0.97 log 10 CFU/ml Staphylococcus aureus was also reported in Tigray region [43]. According to Betelihem and Shimels report, the raw milk samples collected from milking buckets were contaminated by staphylococcus aureus with average count of 7.56×10 2 CFU/ml [44].…”
Section: Staphylococcus Aureus Countsupporting
confidence: 58%
“…In line with this finding, the overall mean count of 4.35±0.97 log 10 CFU/ml Staphylococcus aureus was also reported in Tigray region [43]. According to Betelihem and Shimels report, the raw milk samples collected from milking buckets were contaminated by staphylococcus aureus with average count of 7.56×10 2 CFU/ml [44].…”
Section: Staphylococcus Aureus Countsupporting
confidence: 58%
“…For identification of bacteria to species level, colony morphology and different primary and secondary biochemical testes were employed. The detailed laboratory procedures used for isolation and identification of the bacteria is described elsewhere [5,6,[14][15][16][17][18][19].…”
Section: Laboratory Tests For Bacterial Isolation and Identificationmentioning
confidence: 99%
“…In some countries with low socio-economic status, income growth and urbanization has led to almost doubled consumption of milk and dairy products [1,2]. In Ethiopia, as the dairy industry is developing towards a market-oriented system, majority of milk vendors and cafeterias collect unpasteurized milk from different dairy farms to sell it to consumers [6]. A survey conducted in central Ethiopia reported that 31.8% of farmers consumed raw milk [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…S. aureus has many potential virulence factors and staphylococcus enterotoxin (SE) is one of among several responsible for food poisoning. Ingestion of less than 1.0 μg enterotoxin causes SFP (Seo and Bohach 2007;Enquebaher et al 2015). To date, more than 21 different SEs and SE-like super-antigens have been identified and designated classical as enterotoxins SEA/SEB/SEC/SED/ SEE (SEA-SEE), new (SEG-SEI) and new (SEIJ-SEIV) (Bennett and Hait 2011;Hennekinne et al 2011).…”
Section: Introductionmentioning
confidence: 99%